Operations planning in outpatient chemotherapy with hybrid simulation modelling. (11th January 2023) - Heshmat, Mahmoud; Eltawil, Amr B.; Abdelghany, Mohammed
Outpatient chemotherapy clinics (OCCs) are a crucial medical units where cancer is diagnosed, and treatment is provided. However, they face planning and scheduling challenges. In this paper, two problems in OCCs are addressed: how to accurately compute the utilisation of the nurses, and the patient appointment scheduling problem. An agent-based simulation is used to simulate the nurse activities and thus the nurse utilisation is computed. A discrete event simulation model is developed to evaluate the performance of the current patient appointment practice. However, the resulted nurse utilisation could not be accurately computed. Therefore, a hybrid discrete event and agent-based simulation model is developed to simulate the whole system including the nurse activities. Moreover, the proposed simulation model is used to determine the best patient appointment scenario. The results can be used to accurately compute the nurse utilisation in the OCCs beside the other key performance indicators (KPIs) in OCCs.